2020
DOI: 10.3727/154427220x15845838896323
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Herzberg: Predicting Attendees' Motivation, Satisfaction, and Intention to Revisit a Festival in Cameroon Using an Ordered Logit Approach

Abstract: Festivals have, increasingly, become an important research focus in tourism. This study adaptsHerzberg’s two-factor theory to determine the satisfaction levels of attendees at the Festival ofArts and Culture (FESTAC), held in Limbe, Cameroon. Specifically, it investigated how theabove are influenced by their a priori motivations to attend the event, and how their levels ofsatisfaction, in turn, affect their revisit intentions. Using survey data collected from 324participants at the Festival, the study employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Research suggests that customer loyalty is also measured in terms of intention to purchase. In case of tourism, it is measured in terms of intention to revisit the tourist destination or service provider (Tichaawa and Idahosa, 2020). Service provider plays an extremely important role in co-creating the whole experience for the tourist.…”
Section: Market Mavens and Intention To Revisit Service Providermentioning
confidence: 99%
See 2 more Smart Citations
“…Research suggests that customer loyalty is also measured in terms of intention to purchase. In case of tourism, it is measured in terms of intention to revisit the tourist destination or service provider (Tichaawa and Idahosa, 2020). Service provider plays an extremely important role in co-creating the whole experience for the tourist.…”
Section: Market Mavens and Intention To Revisit Service Providermentioning
confidence: 99%
“…The service provider that has good communication skills and motivates the consumer to participate actively by creating a unique experience will have a greater revisit intention from customer (Abubakar et al, 2017). From the previous literature, it is known that market mavens are highly informed customers who can influence others based on their referral power (Tichaawa and Idahosa, 2020). Market mavens are motivated to share information with other consumers due to a sense of obligation to share information, if they feel satisfied with a product or service (Verboord, 2021).…”
Section: Market Mavens and Intention To Revisit Service Providermentioning
confidence: 99%
See 1 more Smart Citation
“…This framework was later validated in different contexts such as winter tourism (He and Luo 2020) and creative tourism (Dean and Suhartanto 2019), but has not been examined in the context of religious tourism. Other researchers have linked motivation to satisfaction, and hence revisit intentions (Tichaawa and Idahosa 2020). In this space, El-Gohary (2016) claims that religion and spirituality has always been a strong motivator for travel for both pilgrims who wish to seek spiritual attainment and for casual travelers who seek an enriching cultural experience.…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
“…Government backed repetitive cultural events like the Festival of Arts and Culture (FESTAC) hosted annually in the city of Limbe, Cameroon, have the potential to transform the local economy via job creation and revenue generation (Tichaawa, 2016;Tichaawa and Idahosa, 2020). This cultural event is a form of tourism/leisure public service rendered by the government to the community and, as such, has potentials for influencing citizens' perceptions of the government and their trust levels (Christensen and Laegreid, 2005), as relevant research in tourism development studies have shown (see for example Nunkoo, 2017;Nunkoo and Smith, 2013;Tichaawa et al, 2021;Wong et al, 2021;Wong and Lai, 2022).…”
Section: Introductionmentioning
confidence: 99%